ANALISIS GENDER DALAM KARYA SASTRA THE INVENTION OF WINGS KARYA SUE MONK KIDD - rosmiati rosmiati (Prologue: Journal on Language and Literature, 2017)
This research is based on the fact in the literary novel entitled “The Invention of Wings” imaginary form of the family. Gender in thisresearch is based on the construction of the social relations of the menand the women of gender bias. Construction of social nuances patriarchalin the novel as the implications of social context into the reality or thefacts in the literature. there are also the social context in which thebackground is a novel culture highlights issues in SouthGeorgia.Focuseson the analysis of women as representation in the workof literature using gender perspective. Thepublic expression of the formor expressions can become a myth to women. As a result, womenexperienced injustice in the form marginalization, subordination,stereotypes, violence. Women who have experienced injustice in the “TheInvention of Wings” are the daughter grandparent, mother, and Ivory. Thethree of different generations have experienced injustice in a way. It canmake self-awareness in the last two generations of the women. Byshowing the authorities themselves in the men are expected therecognitions and canbe sparedfrom dominance that tends to demeanwomen.